Radiosensitizers in the temozolomide era for newly diagnosed glioblastoma. Issue 3 (30th November 2019) - Mathen, Peter; Rowe, Lindsay; Mackey, Megan; Smart, DeeDee; Tofilon, Philip; Camphausen, Kevin
Abstract: Glioblastoma (GBM) is a challenging diagnosis with almost universally poor prognosis. Though the survival advantage of postoperative radiation (RT) is well established, around 90% of patients will fail in the RT field. The high likelihood of local failure suggests the efficacy of RT needs to be improved to improve clinical outcomes. Radiosensitizers are an established method of enhancing RT cell killing through the addition of a pharmaceutical agent. Though the majority of trials using radiosensitizers have historically been unsuccessful, there continues to be interest with a variety of approaches having been employed. Epidermal growth factor receptor inhibitors, histone deacetylase inhibitors, antiangiogenic agents, and a number of other molecularly targeted agents have all been investigated as potential methods of radiosensitization in the temozolomide era. Outcomes have varied both in terms of toxicity and survival, but some agents such as valproic acid and bortezomib have demonstrated promising results. However, reporting of results in phase 2 trials in newly diagnosed GBM have been inconsistent, with no standard in reporting progression-free survival and toxicity. There is a pressing need for investigation of new agents; however, nearly all phase 3 trials of GBM patients of the past 25 years have demonstrated no improvement in outcomes. One proposed explanation for this is the selection of agents lacking sufficient preclinical data and/or based on poorly designed phase 2 trials. Radiosensitization may represent a viable strategy for improving GBM outcomes in newly diagnosed patients, and further investigation using agents with promising phase 2 data is warranted.